Back to the future: returning to silver-backed money in Sri Lanka - Lebbe, Suhail Sinna; Mohamad, Azhar; Sifat, Imtiaz Mohammad (Emerald Group Publishing Ltd., 2019)
Purpose The purpose of this paper is to investigate the drivers of the behaviour intention to use the Silver-Backed Mobile Payment System (SBMPS) among the residents of Kattankudy, Sri Lanka.